(untitled) (ModaPalavra e-periódico, 2023)
In this article, we intend to baste considerations about the Hundterwasser Spiral, known as the Five Skins Theory, and how to apply it to the fashion system. Thus, the analysis was carried out to verify how this integration happens, the language of fashion through clothing, the construction of the “myself”, and the social identity. The methodology is based on the state of the art, in the perspective of a cosmovision engendered in the relationship of the human being with the environment as a liveable space, the way it determines its existence in harmony with nature through fashion as identity, language, and social representation. It can be said that there is a need for greater human awareness of the environment and that changes in behavior and consumption are necessary. In fashion, to re-signify is necessary.